Pharmacovigilance in Action: Utilizing VigiBase Data to Improve Clozapine Safety - De las Cuevas C; Sanz EJ; de Leon J (Patient Preference and Adherence)
Carlos De las Cuevas,1 Emilio J Sanz,2,3 Jose de Leon4,5 1Department of Internal Medicine, Dermatology, and Psychiatry and Instituto Universitario de Neurociencia (IUNE), Universidad de La Laguna, La Laguna, Canary Islands, Spain; 2Department of Physical Medicine and Pharmacology, Universidad de La Laguna, La Laguna, Canary Islands, Spain; 3Clinical Pharmacology Service, Hospital Universitario de Canarias, La Laguna, Canary Islands, Spain; 4Mental Health Research Center, Eastern State Hospital, Lexington, KY, USA; 5Biomedical Research Centre in Mental Health Net (CIBERSAM), Santiago Hospital, University of the Basque Country, Vitoria, SpainCorrespondence: Carlos De las Cuevas, Department of Internal Medicine, Dermatology, and Psychiatry and Instituto Universitario de Neurociencia (IUNE), University of La Laguna, 38071 San Cristobal de La Laguna, Canary Islands, Spain, Email ccuevas@ull.edu.esPurpose: Clozapine is an antipsychotic which was approved in 1989 for treatment-resistant schizophrenia in the United States (US). There were few randomized trials before its approval and potentially lethal clozapine adverse drug reactions (ADRs), such as agranulocytosis and myocarditis were identified by pharmacovigilance. VigiBase, the WHO global database, is a cornerstone of international pharmacovigilance efforts for ADR identification during post-marketing surveillance. This systematic review of the literature explores additional contributions to the knowledge of clozapine ADRs from recent VigiBase studies.Methods: Using the terms ”clozapine AND VigiBase” we conducted an article search in PubMed on September 5, 2024. Of the 29 articles, 11 were excluded and 18 described in the Results section.Results: All clozapine ADRs were described in two VigiBase studies. One on pregnancy indicated no increased risk with clozapine compared with other antipsychotics; the other reported 191,557 clozapine ADRs, including 22,956 fatal outcomes through January 15, 2023, and paid attention to the reporting style of the top 4 reporting countries (the US, the United Kingdom, Canada and Australia). Infections were described in three VigiBase studies where clozapine treatment was associated with infections, respiratory aspiration, and pneumonia. Rapid titration can lead to localized clozapine-induced inflammations including myocarditis, pericarditis or pancreatitis, or generalized inflammations such as drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome. Clozapine-induced inflammation was described in four VigiBase studies, two focused on all ages (myocarditis and DRESS) and two on youth (myocarditis and another on pericarditis and pancreatitis). Other specific ADRs were described in nine VigiBase studies (hematological malignancies, rhabdomyolysis, sialorrhea, seizures, diabetes mellitus, drug-induced parkinsonism, withdrawal symptoms, and suicidal behaviors).Conclusion: The spectrum of respiratory aspiration – aspiration pneumonia – pneumonia and other infections are significant causes of fatal outcomes in clozapine-treated patients. Clozapine had anti-suicidal effects versus other antipsychotics across all VigiBase labels of suicidal behavior.Plain Language Summary: Why was the review done? Marketers develop a package insert after a medical drug is licensed for use in each country. The package insert describes the known benefits and risks of the drug at the time it was licensed. After licensing, post-marketing studies are continued to look for possible undetected adverse drug reactions; this process is called pharmacovigilance. These pharmacovigilance studies should be done by the drug agencies in all countries. These national agencies send their reports to the international pharmacovigilance database, VigiBase. VigiBase is managed by the World Health Organization and is located in Uppsala, Sweden. Clozapine is a second-generation antipsychotic medication that was licensed in 1989 in the United States for treatment-resistant schizophrenia and then approved by other countries. In 1989 there was major concern about clozapine causing agranulocytosis (loss of white blood cells), so a hematological monitoring system was required in the United States. Later, myocarditis was associated with clozapine in pharmacovigilance studies.What did the authors do? They systematically reviewed VigiBase studies on clozapine adverse drug reactions and identified 18 studies that described clozapine adverse drug reactions in detail.What do these results mean? These VigiBase studies indicate that the respiratory aspiration – aspiration pneumonia – pneumonia spectrum, along with other infections, are significant causes of fatal outcomes in clozapine-treated patients, but this is not mentioned in any clozapine package insert. On the positive side, VigiBase data confirms other literature that clozapine may have specific anti-suicidal effects not present in other antipsychotics.Keywords: clozapine/adverse effects, clozapine/therapeutic use, clozapine/toxicity, drug labeling, product surveillance, postmarketing, schizophrenia